Control and involvement HR practices in Indian call centres: Still searching for answers - Ananthram, Subra; Teo, S.; Connell, J.; Bish, A. (John Wiley & Sons Ltd., 2017)
Call centres were established primarily to reduce organizational costs while simultaneously providing high-quality customer service. To support this 'twin constraints' strategy, a range of human resource (HR) practices tends to be used in call centres that focus simultaneously on both control and involvement. To date, there has been a lack of empirical evidence concerning the outcome of such HR practices on call centre frontline staff (call centre representatives - CCRs). Consequently, this paper attempts to bridge this gap using a sample of 250 CCRs from Indian call centres. The findings show that, while the simultaneous use of involvement-and control-oriented HR practices had a positive impact on CCR job satisfaction, it also resulted in employee exhaustion and disengagement. These findings suggest that while involvement-oriented HR practices enhance CCR job satisfaction, they come at a cost which is potentially a key factor leading to high CCR turnover.